Analisis Kualitas Pelayanan dengan Pemetaan Zone Of Tolerance (Studi Kasus: Saung Angklung Udjo) - Kusumawati, Herlina; Wawolumaja, Rudy (Zenit, 2014)
Saung Angklung Udjo is a tourism spot that provides services concerning the traditional arts of West Java. Based on the interview, Saung Angklung Udjo is facing a problem, namely the declining number of tourists, especially local tourists. Tourists’ satisfaction and the influence of the service tosatisfaction is measured by using service mapping and double regression analysis. Accidental sampling is used as a sampling technique. The number of samples is measured with Hadari Nawawi formula. The result shows that the tourists are not satisfied with the service quality g, yet they still canaccept it. Because all of the services are not satisfactory, the improvement made is based on the significant level of the service toward the overall tourists’ satisfaction. Thus, there are 8 types of services that must be improved.Keywords: Zone of Tolerance, traditional arts, tourists’ satisfaction.